Herlyn-Werner-Wunderlich syndrome: Challenges in diagnosis and management - Roziana, Roziana; Nora, Hilwah; Maharani, Cut R.; Yeni, Cut M.; Dewi, Tengku P.; Rusnaidi, Rusnaidi; Indirayani, Ima; Aditya, Rizka; Al-shather, Zain; Haryani, Siti D. (Narra J, 2023)
Herlyn-Werner-Wunderlich syndrome (HWWS), also known as OHVIRA syndrome (obstructed hemivagina and ipsilateral renal anomaly) is a complex congenital malformation characterized by a triad including uterine didelphys, hemivaginal obstruction, and ipsilateral renal agenesis. In this case report, we present a case of HWWS along with the challenges in diagnosis and multi-step treatment processes. A 25-year-old woman presented to Dr. Zainoel Abidin Hospital in Banda Aceh, Indonesia with a chief complaint of lower back pain for the past six months (two months after the marriage). The patient also complained of late menstruation, followed by thick yellow vaginal discharge resembling malodorous pus occurring after menstruation. Additionally, a history of fever and pain during intercourse was reported. Vaginal examination revealed purulent fluid emerging from a pinpoint hole on the right vaginal wall. Vaginal palpation revealed a two-branched uterus, along with a palpable cystic mass on the right vaginal wall. Ultrasound examination indicated the presence of the right and left hemi-uteri, measuring 4.7x1.35 cm and 5.7x1.26 cm in size, respectively with both ovaries appearing normal. Fluid accumulation was observed in the right hemivagina, while the left kidney exhibited normal features, and the right kidney showed signs of hypoplasia. The patient was diagnosed with uterus didelphys, fluid accumulation in the hemivagina, and right kidney hypoplasia. Magnetic resonance imaging (MRI) confirmed uterus didelphys and revealed narrowing of the right hemivagina, suggestive of HWWS. Hysteroscopy was performed to resect the vaginal septum with laparoscopic guidance, along with drainage of hematocolpos, pyocolpos and placement of an intracervical mold. Despite HWWs having conservative gradual management, it was opted to perform vaginal septum resection, hematocolpos and pyocolpos drainage and placement of an intracervical mould in this case, in order to relieve symptoms and restore the reproductive and sexual functions.